Trade flows and carbon emissions: can we achieve climate targets? - Moghtader, Bardia; Ülengin, Füsun; Gündeş, Eda Helin; Topcu, Y. Ilker; Aktas, Emel (Emerald, 2023)
Policymakers have been calling for actions to meet the UN targets to reduce emissions to 1990 levels. Aligned with the aim of this study, we use a range of machine learning methods to predict the carbon emissions of 30 countries and establish those that are on track to achieve the UN targets. We provide a breakdown of the forecasted freight modal emissions of 23 countries using trade flows. We segment them using K-Means clustering to compare their CO2 emanations. Our findings indicate that only three countries are in line with the mentioned targets. Thus, we propose actions for those that are not.
Keywords: trade flows; carbon emissions; prediction